Spectrophotometric Microdetermination of Thorium(IV) and Uranium(VI) with Chrome Azurol-S in Presence of Cationic Surfactant - A. B. Upase; A. B. Zade; P. P. Kalbende (E-Journal of Chemistry)
Cationic surfactant, cetyldimethylethylammonium bromide (CDMEAB), sensitize the color reactions of Th(IV) and U(VI) with chrome azurol-S(CRAS). Formation of water soluble deeply colored ternary complexes of metal ions show large bathochromic shift. Same stoichiometric composition of ternary complexes with 1:2:4 molar ratio (M-CRAS-CDMEAB) have been observed for both the metal ions and are responsible for enhancement in molar absorptivities and sensitivities at shifted wavelength. The ternary complexes of thorium(IV) and uranium(VI) exhibit absorption maxima at 640 and 620 nm with molar absorptivities 85500 and 69600 L.mol-1.cm-2 respectively. Beer’s law were obeyed in concentration range 0.12-0.185 ppm for Th(IV) and 0.13-0.162 ppm for U(VI) in presence of CDMEAB. Conditional formation constants and various analytical parameters have been evaluated and compared the results of binary and ternary complexes. Enhancement in the molar absorptivities in presence of CDMEAB clearly indicated the usefulness of these colored reactions for microdetermination.